Vacuum ultraviolet photon-mediated production of [F-18]F-2 - Krzyczmonik A; Keller T; Kirjavainen AK; Forsback S; Solin O (WILEY, 2025)
The chemistry of F-2 and its derivatives are amenable to facile aliphatic or aromatic substitution, as well as electrophilic addition. The main limitation in the use of [F-18]F-2 for radiopharmaceutical synthesis is the low specific activity achieved by the traditional methods of production. The highest specific activities, 55GBq/mol, for [F-18]F-2 have been achieved so far by using electrical discharge in the post-target production of [F-18]F-2 gas from [F-18]CH3F. We demonstrate that [F-18]F-2 is produced by illuminating a gas mixture of neon/F-2/[F-18]CH3F with vacuum ultraviolet photons generated by an excimer laser. We tested several illumination chambers and production conditions. The effects of the initial amount of [F-18]F-, amount of carrier F-2, and number of 193-nm laser pulses at constant power were evaluated regarding radiochemical yield and specific activity. The specific activity attained for [F-18]F-2-derived [F-18]NFSi was 10.3 +/- 0.9GBq/mol, and the average radiochemical yield over a wide range of conditions was 6.7% from [F-18]F-. The production can be improved by optimization of the synthesis device and procedures. The use of a commercially available excimer laser and the simplicity of the process can make this method relatively easy for adaptation in radiochemistry laboratories.